Francesco Collura with contributions by Sergio Cascella, Emiliano Arena and Benedetto Caroccio, Studia Calactina I. Ricerche su una città greco romana di Sicilia: Kalè Akté – Calacte. - Bergemann, Johannes (Journal of Greek Archaeology, 2019)
The Tyrrhenian north coast of Sicily is in its eastern part, and apart from Tyndaris and Alaesa, archeologically far less explored than the south and east coast with its numerous Greek settlements. The new publication about Kale Akte is therefore very welcome. The city is located about 100 km west of Milazzo and about 60 km east of Cefalù, the ancient Kephaleodium. In the immediate vicinity are Halesa, about 20 km west, Apollonia (San Fratello) 20 km, Aluntium (San Marco d’Alunzio) 30 km and the villa of Patti Marina 60 km east.